The Protection of Human Rights for Children and Women from the Houthi Insurgency - Emier Azka, Mohammed; Iskandar, Muhammad Yusuf; Azyzy Amyrul Hafidz Hamam, Muhammad; Syahnur, Lutfiah; Syahriani, Fadilla (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The ongoing Houthi insurgency in Yemen has led to severe humanitarian impacts, particularly affecting women and children as the most vulnerable groups. This research aims to examine the protection of human rights for women and children amidst continuous violations committed by the Houthi armed movement. Using a qualitative field research approach, the study is based on direct interviews with humanitarian workers, legal experts, and victims, supported by the analysis of human rights reports and international legal instruments. The findings reveal that despite the existence of frameworks such as the Convention on the Rights of the Child and CEDAW, protection remains ineffective due to political instability, the dominance of non-state actors, and limited access for humanitarian organizations. Key violations include child soldier recruitment, sexual violence, forced displacement, and denial of access to education and healthcare. The study concludes that stronger international monitoring mechanisms, targeted sanctions, and the integration of gender- and child-sensitive frameworks into Yemen’s peacebuilding agenda are urgently needed. This study contributes a field-based legal analysis of the systemic failures in protecting the rights of women and children in armed conflict, and emphasizes the importance of a more effective international legal response in the context of the dominance of non-state armed actors.